Contact and Conflict: Polish-Jewish Contact Zone - Prokop-Janiec, Eugenia (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The article suggests using the category of the contact zone adopted from postcolonial studies in research on borderland, which - in turn - allows researchers to describe the phenomenon of the frontier. According to Pratt, contact zone may be understood as the space of cooperation and competition, coexistence and antagonism, contact and conflict of groups. The aim of the article is to analyse the representations of borderland in Polish-Jewish prose of the 1930s (including the novels published in the mass-circulation press). We shall focus on the motives that stand behind the conflictive communication. It is worth noting that in the literary renditions, interactions between Poles and Jews easily transform into conflicts. Conflictive communication appears in various places (e.g. school, street, neighbourhood), forms (nicknames, arguments, pogrom cries) and functions (from initiating and escalating tensions to riots and murders). As a result, the contact zone transforms into a conflict zone.
Translated by Agnieszka Grząśko.
Keywords: Polish-Jewish frontier; contact zone; Polish-Jewish prose; conflictive communication